'In the Land of the Blind, the One-eyed is King': Some Pedagogical Foundations for Deep, Practical Online Student Learning. Issue 2 (November 2015) - Mudge, Peter
Abstract : All those involved in teaching and learning, whether lecturers or their students, are likely to have one or more 'blind spots'. These blind spots can materialize without warning in areas such as ways of knowing, pedagogical frameworks, or even the types of teaching strategies one selects for face-to-face, blended or online teaching contexts. This article draws examples from online courses designed and taught by the author (principally to RE teachers in primary and secondary schools), and argues that course lecturers and their students alike need to examine and critique certain background assumptions to teaching and learning, their pedagogical models and ways of knowing, along with the practical teaching and learning strategies that they select to support these areas. The two courses referred to are EDUC6043, Religious education: theory and practice, and RELT6016, Spiritualities, practices and values. Two teaching approaches explored in more detail are personal, reflective writing, and project-based learning.